PENGARUH SUBSTITUSI DEDAK DENGAN TEPUNG AMPAS KELAPA TERFERMENTASI TERHADAP PERTUMBUHAN DAN EFISIENSI PAKAN IKAN PATIN (Pangasius sp.) - Yespus .; Mohamad Amin; Yulisman . (Jurnal Akuakultur Rawa Indonesia, 2018)
ABSTRACTCoconut dregs is waste from coconut milk production. The purpose of this study was to determine the effect of fermented coconut dregs feeding on the growth and efficiency of catfish feed and to know the exact percentage in feed formulation on catfish. This research was conducted from November to December 2017 at Aquaculture Laboratory of Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University. This study used a complete randomized design with 5 treatments and 2 replications. The treatment was used the difference of percentage of the fermented coconut dregs flour in the formulation of 0%, 5%, 10%, 15% and 20%. Data to be collected include growth, survival, feed efficiency, formulated analysis of each treatment consisting of water, ash, protein, fat, carbohydrate, and crude fiber and water quality. The result of this research showed that the absolute growth of lengthy P4 is 0.54 cm, the absolute growth of weight P4 is 1.42 g, the best feed consumption in P0 with total feed consumption is 3.43 g.individu-1, feed efficiency P4 is 47.82% and survival rate P4 is 87.50%. Water quality during research were still optimum for catfish with temperature 26.0-29.0oC, pH 6.5-8.1, DO 4.57-8.86 mg.L-1 and ammonia 0.003-0.02 mg.L-1. Keywords: Catfish, Coconut dregs, Feed efficiency, Fermentation, Growth